2017
DOI: 10.18869/acadpub.jpcp.5.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Testing Older Adults for Signs of Age-Related Cognitive Decline: Clock Drawing Test vs.Mini-Mental State Examination

Abstract: Objective: Mini-mental state examination, a nonspecific measure of global cognitive function, and the clock drawing test, a very concise and specific measure of cognitive function, are among the most widely used screening tests for cognitive dysfunction. The present research aimed to examine the correspondence between MMSE and CDT scores. Methods:A total of 70 older adults (mean(SD) age=69.70(6.41) y) were selected by convenience sampling method from two local health centers from the same civil servant area in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…We have examined the cognitive decline among enrolled participants using both MMSE and Mini-Cog Scores, and it was tracked with respect to age, the mean MMSE score decreased from 26.58 among young adults to 24.06 among older adults, and the same was with the mean Mini-Cog Scores (Figure 1 & 2). This is also supported by the results of a similar study, participants < 75 years of age had the mean MMSE score of 28.14 while those > 75 years had a mean score of 27.81 and CDT declined from 4.47 to 4.19 among the two age groups 4 . In addition to age, the effects of gender, educational levels, and occupational load on cognitive functioning were also investigated.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…We have examined the cognitive decline among enrolled participants using both MMSE and Mini-Cog Scores, and it was tracked with respect to age, the mean MMSE score decreased from 26.58 among young adults to 24.06 among older adults, and the same was with the mean Mini-Cog Scores (Figure 1 & 2). This is also supported by the results of a similar study, participants < 75 years of age had the mean MMSE score of 28.14 while those > 75 years had a mean score of 27.81 and CDT declined from 4.47 to 4.19 among the two age groups 4 . In addition to age, the effects of gender, educational levels, and occupational load on cognitive functioning were also investigated.…”
Section: Discussionsupporting
confidence: 76%
“…Another study suggested that physical frailty has a significant impact on cognitive activities and mental health 28 . As per our results, the occupational load was significantly associated with cognitive performance, and participants with low to moderate occupational load had mild to severe cognitive impairment as compared to those with high occupational load ( Table 3 & 4). The educational level also had a significant impact on the cognitive abilities of the participants (p < 0.05).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The cut-off point (in seconds) for average-normal performance was set at one standard deviation above the mean (+ 1SD), for slower than normal between + 1 and + 2 standard deviations, and for abnormal performance at more than + 2 standard deviations for English and Swedish [16,17]. Its test-retest reliability was reported as 0.89 [22]. In Iran the MMSE psychometric properties showed that the test-retest reliability is 0.78 and its cut-off point is 21.…”
Section: Measurementsmentioning
confidence: 99%